2015
DOI: 10.1093/chromsci/bmt034
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Cortisol, Cortisone, 6 -Hydroxycortisol and 6 -Hydroxycortisone by HPLC

Abstract: A specific and sensitive method based on high-performance liquid chromatography with ultraviolet absorbance detection (HPLC-UV) was developed for the simultaneous determination of urinary cortisol (F), cortisone (E), 6β-hydroxycortisol (6β-OHF) and 6β-hydroxycortisone (6β-OHE) using dexamethasone as the internal standard. The method involved solid-phase extraction of the five compounds from urine using Oasis HLB Waters cartridges with an elution solvent of ethyl acetate-diethyl ether (5 mL; 4:1, v/v), followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Our previous experiments confirmed that the combined ratio of 6β-hydroxycortisol and 6β-hydroxycortisone to cortisol and cortisone in urinary MR reflects CYP3A4 catalytic ability and not the total activity of CYP3A4 and CYP3A5 isoforms (unpublished data). Another previous study completed by our laboratory showed that the MR was significantly related with the dose-corrected trough concentrations (C 0 /D) of Tac in renal transplant recipients (r= -0.824, P<0.05) [11] .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous experiments confirmed that the combined ratio of 6β-hydroxycortisol and 6β-hydroxycortisone to cortisol and cortisone in urinary MR reflects CYP3A4 catalytic ability and not the total activity of CYP3A4 and CYP3A5 isoforms (unpublished data). Another previous study completed by our laboratory showed that the MR was significantly related with the dose-corrected trough concentrations (C 0 /D) of Tac in renal transplant recipients (r= -0.824, P<0.05) [11] .…”
Section: Introductionmentioning
confidence: 76%
“…The 6β-OHF, 6β-OHE, F and E in urine were measured using the HPLC-UV method developed in our laboratory [11] . The lower limit of quantification was 5 μg/L for all of the compounds in the urine.…”
Section: Analytical Methods 6β-ohf 6β-ohe F and E In Urinementioning
confidence: 99%
“…6β‐Hydroxycortisol, 6β‐hydroxycortisone, F, and E in urine were measured using the HPLC–UV method developed in our laboratory . The lower limit of quantitation (LLOQ) was 5 μg L −1 for all compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary 6β‐OHF and cortisol concentrations have been measured using immunochemical, high‐performance liquid chromatography (HPLC), and liquid chromatography/tandem mass spectrometry (LC‐MS/MS) methods . We previously developed a reliable capillary gas chromatography/MS method for determining both 6α‐OHF and 6β‐OHF concentrations in urine using stable isotope‐labeled analogs as internal standards .…”
Section: Introductionmentioning
confidence: 99%